Testing the Pharmacokinetic Interactions of 24 Colonic Flavonoid Metabolites with Human Serum Albumin and Cytochrome P450 Enzymes - Mohos, Violetta; Fliszár-Nyúl, Eszter; Lemli, Beáta; Zsidó, Balázs Zoltán; Hetényi, Csaba; Mladěnka, Přemysl; Horký, Pavel; Pour, Milan; Poór, Miklós (Biomolecules, 2020)
Flavonoids are abundant polyphenols in nature. They are extensively biotransformed in enterocytes and hepatocytes, where conjugated (methyl, sulfate, and glucuronide) metabolites are formed. However, bacterial microflora in the human intestines also metabolize flavonoids, resulting in the production of smaller phenolic fragments (e.g., hydroxybenzoic, hydroxyacetic and hydroxycinnamic acids, and hydroxybenzenes). Despite the fact that several colonic metabolites appear in the circulation at high concentrations, we have only limited information regarding their pharmacodynamic effects and pharmacokinetic interactions. Therefore, in this in vitro study, we investigated the interactions of 24 microbial flavonoid metabolites with human serum albumin and cytochrome P450 (CYP2C9, 2C19, and 3A4) enzymes. Our results demonstrated that some metabolites (e.g., 2,4-dihydroxyacetophenone, pyrogallol, O-desmethylangolensin, and 2-hydroxy-4-methoxybenzoic acid) form stable complexes with albumin. However, the compounds tested did not considerably displace Site I and II marker drugs from albumin. All CYP isoforms examined were significantly inhibited by O-desmethylangolensin; nevertheless, only its effect on CYP2C9 seems to be relevant. Furthermore, resorcinol and phloroglucinol showed strong inhibitory effects on CYP3A4. Our results demonstrate that, besides flavonoid aglycones and their conjugated derivatives, some colonic metabolites are also able to interact with proteins involved in the pharmacokinetics of drugs.
Keywords: hepatocyty; Flavonoids; erytrocyty; flavonoidy; Hepatocytes; lidé; Serum Albumin, Human; Erythrocytes; Cytochrome P-450 Enzyme System; systém (enzymů) cytochromů P-450; lidský sérový albumin; Humans